Perception On Corporate Retail Outlet On Consumers In Salem City (International Journal of Scientific Research and Management (IJSRM), 2017)
Organized retailing in India initially began in the South. The availability of land at prime locations coupled with lower real estate prices (compared to Mumbai and Delhi) made multi-storeyed shopping complexes possible. Retailing is one of the fastest growing industries in India, catering to the world’s second-largest consumer market. Objectives of the study To analyse demographic factors and impact of corporate retailers on consumers in Salem City. Methodology of the study, Primary data as well as secondary data was used in this study. The researcher collected data by using a convenience sampling method. The researcher conducted the survey for 6 months i.e., from January 2013 to June 2013. Findings of the study, it is clear that 90 per cent of consumers in the food category are satisfied, 6 per cent highly satisfied and 4 per cent are undecided. 75 per cent of consumers in the Textile category are satisfied, 21 per cent highly satisfied and 4 per cent are undecided. Suggested in this study, In the general opinion among the educated is that the small traders are doing adulteration. For this reason they prefer corporate retail for purchase. Therefore the small traders should avoid the practice of the adulteration, otherwise survival will be difficult. Concluding in this study, The decision is fuelled by booming economy and the positive reports of leading retail assessors of the world